Social enterprises and development management a socialist partnership between state and non-state duty bearers and social service providers in Vietnam - Nam, Pham Tien; Ferrer, Oscar P. (2014)
In the context of the fiscal tightening of the Vietnamese Government to reduce its debt, the state leadership has encouraged social enterprises to undertake initiatives that support the comprehensive sustainable development of the country. People's engagement in social reconstruction and development is indispensable. Social enterprises in Vietnam have social development orientation and play an important role in the provision of social services, in particular, to vulnerable groups. Business activit6ies serve as tools to meet social objectives by reinvesting profit generated to cause-oriented organizations and underprivileged communities. Thus the objective of this study is to determine how selected social enterprises in Vietnam function as non-state partners in nation-building by providing social services to young people. Utilizing a qualitative descriptive research methodology, this study features case studies of three social enterprises in Hanoi City, namely, Hoa Sua School of Economics and Tourism, Know One, Teach One (KOTO) and Tea Talk. By analyzing their experiences, the study aims to contribute to the study and practice of social development administration and participatory governance in a socialist country like Vietnam.
Keywords: Social enterprises -- Vietnam -- Case studies; Social entrepreneurship -- Vietnam; Social responsibility of business -- Vietnam